2007
DOI: 10.1177/1545968307302923
|View full text |Cite
|
Sign up to set email alerts
|

Using Kinematic Analysis to Evaluate Constraint-Induced Movement Therapy in Chronic Stroke Patients

Abstract: The method of kinematic analysis was sensitive for an assessment of motor recovery induced by CIMT. The kinematic results suggest that the increase in the use of the paretic limb in activities of daily living after the intervention is not only attributable to the patient's increased attention to it and better hand dexterity, but it is also a consequence of the improved speed of movement and better coordination between shoulder and elbow joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
154
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(162 citation statements)
references
References 39 publications
6
154
1
1
Order By: Relevance
“…The responsiveness of the WMFT-FAS was larger than that of the WMFT-TIME in this study. This result is contrary to the findings of Caimmi et al, 57 who concluded that responsiveness measured by the effect size d was moderate for the WMFT-TIME and trivial for the WMFT-FAS. Although different indices and different treatment protocols were used in these 2 studies, the larger variance of the WMFT-TIME among our patients may have contributed to our results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The responsiveness of the WMFT-FAS was larger than that of the WMFT-TIME in this study. This result is contrary to the findings of Caimmi et al, 57 who concluded that responsiveness measured by the effect size d was moderate for the WMFT-TIME and trivial for the WMFT-FAS. Although different indices and different treatment protocols were used in these 2 studies, the larger variance of the WMFT-TIME among our patients may have contributed to our results.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, because functional imaging and kinematic analysis have been suggested to be surrogate outcome measures for evaluating the efficacy of CIT and other rehabilitation techniques, 57,58 the correlations between changes in the clinical measures of motor function and changes in functional imaging and kinematic performance need to be studied in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…the time derivative of acceleration, has been used as an empirical measure of movement smoothness (Casadio et al, 2010). In this study, NJ was tested as a measure of the quality of selective motor control and was used to evaluate the qualitative features of the multi-joint upper limb movements, considering its inverse correlation with the smoothness of hand movement (Flash and Hogan, 1985;Caimmi et al, 2008). Our data bring out additional evidence regarding the recovery process after neurological damage, which is reflected in the execution of progressively smoother movements as confirmed by a significant reduction in NJ (Krebs et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…N vp , which represents the number of corrective attempts made mid-movement, is also a surrogate marker that has been used in publications. (4,5) The use of virtual reality-based therapy to augment poststroke upper limb recovery ABSTRACT Stroke remains one of the major causes of disability worldwide. This case report illustrates the complementary use of biomechanical and kinematic in-game markers, in addition to standard clinical outcomes, to comprehensively assess and track a patient's disabilities.…”
Section: Case Reportmentioning
confidence: 99%